Analysis Of The Environmental Impact Of Floating Net Cage Waste On The Water Quality Of Ekas Bay West Nusa Tenggara Province, Indonesia - Lalu Kinayung Purbajati; Heri Murtawan; Samsul Bahri; Charlis Palupi; Alfian Pujian Hadi; Firman Ali Rahman (Yayasan Tajuk Indonesia, 2024)
The living environment given by God Almighty to the Indonesian people is a gift that must be developed and preserved. The aim is that the environment can support the lives of the nation, people and other living creatures and improve the overall quality of life. Floating Net Cage technology is a very productive and intensive aquaculture method, with a structure consisting of several net cages placed on floating rafts in coastal waters. This article was written using the library research method, namely by codifying scientific sources from various journals and articles with the same data and then combining them to obtain information about the impact of feed waste from floating net cage cultivation. Intensive cultivation in floating net cage produces waste that is discharged into the aquatic environment and can significantly affect water quality. The waste load from floating net cage cultivation can cause the loss of seagrass beds (Posidonia oceanica). Another impact is a decrease in the diversity of infauna in sediments and degradation of the bottom of the waters. Steps that can be taken to prevent environmental pollution in floating net cage cultivation are by paying attention to several aspects such as the use of quality and effective feed, and minimizing leftover feed that is wasted into the sea and using the right amount thus reducing pollution.